Nutritional Composition and In-Vitro Analysis of Common Forages Used in Smallholder Goat Farms in Lombok, Indonesia - Azhary Noersidiq; Muhamad Amin; Oscar Yanuarianto; Ryan Aryadin Putra; M Fauzi Nugroho (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
The research was conducted in Lombok Island, Indonesia. Samples of forages were collected from smallholder goat farms across three regencies, i.e., East Lombok, Central Lombok, and West Lombok. The selection of respondents was carried out using a purposive sampling method, whereby locations based on their relevance to smallholder goat farming activities and the availability of diverse forage resources commonly utilized by farmers. Data obtained from chemical composition and in-vitro analysis were subjected to descriptive statistics analyses, including mean and standard deviation (mean+sd). Eight forage species, including Leucaena leucocephala, Indigofera zollingeriana, Artocarpus heterophyllus, Hibiscus tiliaceus, Terminalia catappa, Jatropha curcas, Lannea coromandelica, and Native grasses, were analyzed for nutrirional composition and in-vitro analysis. Results showed significant variation among species. Leguminous forages, particularly Leucaena leucocephala and Indigofera zollingeriana, had superior nutritional profiles with high crude protein (31-40%), low neutral detergent fiber (19-35%), and high total digestible nutrients (>75%). These species also exhibited the highest in-vitro dry and organic matter digestibility (IVDMD >60%) and also produced rumen ammonia concentrations within the optimal range (9–11 mmol/L), indicating efficient microbial activity and nitrogen utilization. In contrast, non-leguminous forages and Native grasses contained higher fiber and lignin, resulting in lower digestibility (<35%) and reduced rumen ammonia levels (<6 mmol/L). In conclusion, leguminous forages, especially Leucaena leucocephala and Indigofera zollingeriana, showed the highest nutritional composition and digestibility, characterized by high crude protein, low fiber, and high in-vitro digestibility. These species also produced optimal rumen ammonia levels, indicating efficient nitrogen utilization and superior rumen fermentation Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 12: Responsible Consumption and ProductionSDG 15: Life on Land